O conteúdo constitucional da liberdade de associação - Pinheiro, Flavia de Campos (2008)
The freedom of association as a fundamental right is one of the characteristics of individual freedom. It is the right of collective exercise that, through a combination of efforts, aims to achieve a common and edifying goal. The understanding of the constitutional content of the freedom of association derives from the gathering of some elements which characterise this freedom, and they comply with the legal system. In addition to this, in order to guarantee its effectiveness, one needs to consider the instruments which allow the individual the full enjoyment of this freedom. The thesis foresees to the association a set of elements, rights, instruments and prohibitions which identifies the constitutional characteristic of such freedom. Furthermore, it studies the limitation of state power and the juridical security for its existence. The topic was developed on the grounds of the importance that the freedom of association, if well applied, seems to have in relation to the effectiveness of other rights, equally fundamental, and it aspires to achieve democracy. Therefore, it is necessary to recognise the constitutional content of the freedom of association in order to use